BASIC PRINCIPLES OF MORAL RULES AND VALUES - Lalikhon Mukhamedzhanova (Scholar Express Journal, 2025)
This article examines the role of ethical norms and values in society, as well as their fundamental principles. Based on the views of various philosophical movements and thinkers, the formation and development of moral values are analyzed. Additionally, the significance of ethical principles in modern society and their relevance are discussed.
Keywords: ethics; values; principles; philosophy